The Effect of Partnership Strategy on Business Success (Case Study on Hospitality in West Java) - Halimah Zahrah; Agus Rahayu; Puspo Dewi Dirgantari (Journal of Accounting and Finance Management, 2022)
The phenomenon in the hotel industry, which at the time of this endemic began to rise, made hotel entrepreneurs or managers take advantage of partnerships to increase profits. The benchmark for the success of the company is judged by the small number of problems that occur in the company. This study aims to obtain findings about whether or not the influence of the partnership strategy is suspected on business success. This type of research is descriptive quantitative. The unit of analysis studied were hotel owners in West Java who are members of the Indonesian Hotel and Restaurant Association in the West Java region. The population was taken from the number of hotel entrepreneurs in West Java who are members of the West Java hotel and restaurant business association on instagram @phrijabar as many as 134. The sampling technique uses purposive sampling, because the data source collection technique is carried out by determining a sample of certain considerations. Technical Data Analysis using Simple Linear Hypothesis-Regression Test by testing the Coefficient of Determination, T Test, F Test. Instrument Test using Validity & Reliability analysis. The results of the study found that rejecting H 0 and accepting H 1 which states that there is a significant contribution between the partnership strategy variables on business success in hospitality in West Java. All indicators of these two variable items are valid. The Cronbach's Alpha value of the two variables is realible. This will have an impact on increasing profits, increasing customers and increasing sales.